ORGANIZING STRATEGIC MANAGEMENT TO ENHANCE THE EFFECTIVENESS OF INNOVATION ACTIVITIES IN INDUSTRIAL ENTERPRISES - Asimova Feruza Abdusattorovna; Zagidullina Kamila Rafailovna; Sayfutdinova Nigina Furkatovna (Ecominds Press, 2025)
This article examines the importance of strategic management in enhancing the effectiveness of innovation activities in industrial enterprises. Innovations are a crucial factor for ensuring competitiveness, economic growth, and sustainable development. By effectively organizing strategic management, enterprises can increase their innovation potential, develop new products and technologies, and improve production processes.
Keywords: industrial enterprises, innovation activities, strategic management, effectiveness, competitiveness, economic growth, technologies, products, management strategies, organizational changes, leadership, innovation potential, global market, strategic decisions.